Analysis of Parking Needs at Kertapati Station - Malaiholo, David; Wardani Puruhita, Hana; Yuda Pradana, Ikhsal (ASTONJADRO, 2023)
The increasing population, rapid development, increasing number of motorized vehicles and increasing community activities are part of the current transportation problem. These problems can have an impact on improving the need for parking. At Kertapati Station there is a parking space facility. Provision of parking space if not appropriately arranged can be a problem and interfere with the level of comfort in the service process and can result in traffic jams, especially at stations. This study aims to analyze parking needs at Kertapati Station, and project parking needs at Kertapati Station for the next 5 years. The research method used is the observation of parking when vehicles enter and exit the train station. The research was conducted for three days, Thursday to Saturday April 28-30 2022 with an observation time of 07.00-21.30 WIB. From the results of the data analysis, it is known that the largest parking space requirement occurs on Saturday 30 April 2022 for motorcycles of 177.86 SRP, and passenger cars as much as 86.42 SRP. The projection within 5 years is that in 2025 the need for parking space for motorbikes can still accommodate the number of vehicles of 177 SRP while for passenger cars there is a shortage of parking space of 49 SRP.